Analisis Peran Fungsi Pengawasan/Controlling dalam Media Dakwah - Asari, Syafna; Efendi, Erwan; Yamin, M; Al-Baihaqi, Mahatir; Saputra, Parlin; Ardiansyah, Ardiansyah (Peneliti.net, 2024)
This journal reviews various types of media that can be used as a tool for conveying da'wah messages because currently da'wah cannot rely on traditional methods alone. The role of the supervisory function in the da'wah media is as a form of monitoring or ensuring that there are no mistakes in the da'wah delivered through the da'wah media. The type of research used is literature study with sources from journals, articles and book references which serve as a strong basis for the results and discussion. The process of using this method makes it easier to search for various information. So analyzing the role of the supervisory function in da'wah media is easier to understand.